School guidance and counselling in Natal : present realities and future possibilities - Naicker, Dhanasagaran (Rhodes University, Faculty of Education, Department of Education, 1993)
School guidance and counselling is a programme that is complementary to the education process and is seen as a support service for the pupil. However, owing to the apartheid policies of the South African government, all pupils did not have equal access to guidance services. In a post-apartheid South Africa it is anticipated that a unitary education system would emerge to provide equal access to education for all South African pupils and this implies that previous imbalances that existed would have to be addressed. In this study the present state of guidance and counselling services in Natal was investigated and policy options to redress past inequities and to make school guidance and counselling services a reality for all South African pupils, within the context of limited resources were explored.
Keywords: Educational counseling -- South Africa; Counseling -- Vocational guidance -- South Africa